Khejri (Prosopis cineraria L. Druce) based agroforestry systems in the arid and semi-arid region: Supporting ecosystem services - Kaushik, N.; Arya, S.; Yadav, P.K.; Bhrdwaj, K.K.; Gaur, R.K. (Indian Journal of Agroforestry, 2021)
Khejri (Prosopis cineraria) is grown widely in tropical and sub-tropical lands around the globe because of its drought tolerance and capacity to withstand heavy lopping. Khejri based agroforestry systems i.e. traditional and copied/manipulated from traditional systems were assessed for ecosystem services. The information on different aspects of Khejri and its ecosystem services was collected through several documents on subject sourced through web and relevant articles of select journals. The authors also visited the traditional Khejri based agroforestry fields in the area and made observations on ecosystem services provided. The data were collected for provisioning, regulating, supporting, aesthetic and religious services. Khejri based agroforestry systems were found to provide all ecosystem services. In total, we identified 14 services provided by Khejri based agroforestry. Khejri based agri-silvicultural and agri-silvi-horticultural systems provided more services and profits than sole cropping or other land-use systems in the region. Soil fertility and organic matter were also more under Khejri based agroforestry system as compared to other systems. Khejri based agroforestry enhanced the farm income, improved soil fertility, provided nutrition and resilience under hostile climatic conditions without degradation of land and other natural resources. Identification of possible ecosystem services from Khejri based agroforestry systems in this review will provide an instrument to the policymakers for assessing monetary outcomes of Khejri based agroforestry systems.